Combined transcriptome and metabolome analyses to understand the dynamic responses of rice plants to attack by the rice stem borer Chilo suppressalis (Lepidoptera: Crambidae). Issue 1 (December 2016) - Liu, Qingsong; Wang, Xingyun; Tzin, Vered; Romeis, Jörg; Peng, Yufa; Li, Yunhe
Abstract Background Rice (Oryza sativa L.), which is a staple food for more than half of the world's population, is frequently attacked by herbivorous insects, including the rice stem borer, Chilo suppressalis. C. suppressalis substantially reduces rice yields in temperate regions of Asia, but little is known about how rice plants defend themselves against this herbivore at molecular and biochemical level. Results In the current study, we combined next-generation RNA sequencing and metabolomics techniques to investigate the changes in gene expression and in metabolic processes in rice plants that had been continuously fed byC. suppressalis larvae for different durations (0, 24, 48, 72, and 96 h). Furthermore, the data were validated using quantitative real-time PCR. There were 4, 729 genes and 151 metabolites differently regulated when rice plants were damaged byC. suppressalis larvae. Further analyses showed that defense-related phytohormones, transcript factors, shikimate-mediated and terpenoid-related secondary metabolism were activated, whereas the growth-related counterparts were suppressed byC. suppressalis feeding. The activated defense was fueled by catabolism of energy storage compounds such as monosaccharides, which meanwhile resulted in the increased levels of metabolites that were involved in rice plant defense response. Comparable analyses showed a correspondence between transcript patterns and metabolite profiles. Conclusion The current findings greatly enhance our understanding of the mechanisms of induced defense response in rice plants againstC. suppressalis infestation at molecular and biochemical levels, and will provide clues for development of insect-resistant rice varieties.